KOGNITIF DEVELOPMENT: Mencermati Siklus Pertumbuhan Kognitif Anak - Khulusinniyah Khulusinniyah (LP2M Universitas Ibrahimy, 2016)
Cognitive development should be considered early, because without the appropriate stimulation these aspects can’t develop optimally. Cognitive development in early childhood is part of efforts of capability development of cognitive development in general such as auditory, visual, tactics, kinesthetic, arithmetic, geometry, and science, so that in the end of learning the child is able to develop their power of perception based on what is seen, heard and felt either naturally or scientifically so that children have a comprehensive understanding and can answer the problems that faced by them